2021
DOI: 10.1093/jpids/piab035
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in a Subset of Hospitalized Children in Israel

Abstract: Background Most pediatric coronavirus disease 2019 (COVID-19) is mild. We assessed nationally severe COVID-19, including pediatric inflammatory multisystem syndrome (PIMS), in hospitalized children. Methods An ongoing, prospective, national surveillance was conducted from March 2020 through March 2021, at 20 hospitals treating children <18 years across Israel (~75% of Israeli hospitals). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 22 publications
(26 reference statements)
1
23
0
Order By: Relevance
“…The majority of children (60-70%) were admitted to intensive care units. According to that report, the prevalence of MIS-C in the United States was approximately 1:3200 of SARS-CoV-2-positive children and adolescents, similar to the reported prevalence in Israel [6].…”
Section: Multisystem Inflammatory Syndrome In Children (Mis-c)supporting
confidence: 56%
See 3 more Smart Citations
“…The majority of children (60-70%) were admitted to intensive care units. According to that report, the prevalence of MIS-C in the United States was approximately 1:3200 of SARS-CoV-2-positive children and adolescents, similar to the reported prevalence in Israel [6].…”
Section: Multisystem Inflammatory Syndrome In Children (Mis-c)supporting
confidence: 56%
“…Mortality was 1-2%. An Israeli study showed similar findings: during the first three waves of the COVID-19 pandemic, 56% of children diagnosed with MIS-C were admitted to intensive care units and 20% required mechanical ventilation [6].…”
Section: Multisystem Inflammatory Syndrome In Children (Mis-c)mentioning
confidence: 65%
See 2 more Smart Citations
“…32,33 Among the hospitalized patients, the MIS-C rate varies between 10 to 25%. 34 Currently, no long-term follow-up studies that define with certainty the prognosis of patients with MIS-C are reported. In a systematic review including 16 studies and a total of 655 MIS-C patients, 10% of patients (68) required critical care, and the mortality rate was 1.7% (11 deaths ).…”
Section: Sars-cov-2 Infection and Covid-19 In Children Andmentioning
confidence: 99%